Aspek Hukum Penggunaan Bilyet Giro Kosong Dalam Transaksi Jual Beli - Imroatul Hasanah; Nazatul Inayah; Sumriyah Sumriyah (Khirani: Jurnal Pendidikan Anak Usia Dini, 2023)
At present, the rapid development of world economy and trade makes most people more inclined to take practical measures such as checks and demand deposits. We see that with a giro, the parties can carry out different transactions, resulting in rights and obligations between the parties. However, it is very unfortunate that in daily practice, especially in buying and selling, the use of this giro as a payment method is still common with blank giro. The problem is what is the legal position of using blank giro in buying and selling transactions and what are the legal consequences of using blank giro in buying and selling transactions. This study uses a normative legal approach. With an empty giro, the buyer will be considered negligent or commit fraud if the account is closed. In regulating Bilyet Giro we need real provisions regarding fraud, such as article 378 of the Criminal Code, and acts of default, such as article 1365 of the Civil Code. In addition, to avoid misuse of parties with bad intentions, namely increasing efficiency in administrative management.